(untitled) (Research, Society and Development, 2024)
This article aimed to analyze conceptions and characteristics of self-injury without suicidal ideation - ASIS and deepen the discussion regarding this theme in the school context. This work is part of an investigation with a qualitative and quantitative approach, through a case study developed within the scope of a doctoral thesis. The contributions of this study lie in bringing a necessary theme to the educational field and understanding what education professionals think about ASIS and what they need to know, in a prospective view of preventive and empathetic actions with adolescent students. The results of this study suggest that the definition of ASIS be fruitfully discussed in the educational field, especially in relation to similarities and differences in suicidal behavior; that taboos and fear of talking about the subject be replaced by the courage to help; that the reflections presented point out ways for school officials to know how to deal with students suspected or engaged in ASIS and that they serve as seeds in fertile ground for further research on the subject.